Pengaruh Layanan Penguasaan Konten Terhadap Kecerdasan Emosional - Putri, Nisrina (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Monks (1999:263), states that "hormonal stimulation causes a feeling of unease in adolescents which can lead to unstable, sometimes uncontrollable, emotions." Monks (1999: 279) adds that: The start of adolescence is a clear change and provides specific characteristics and even its own culture, this group of teenagers during puberty try to escape from parental control. His ego becomes high, he wants as much freedom as possible, he tends to get sad easily, he often looks for his identity in despair. This process is a process of searching for ego identity which can influence learning achievement so that learning achievement is not optimal. By having high emotional intelligence, students will be able to improve their academic achievement scores and their learning achievements will be better In providing an understanding of emotional intelligence to students, guidance and counseling teachers can use content mastery services, namely Content Mastery Services (PKO) which are assistance services for individuals (students) either individually or in groups to master certain abilities or competencies through learning activities. certain things that are useful for supporting understanding and daily life for emotional development both as individuals and as students and for consideration in making certain decisions or actions. This is in line with the aim of choosing the type of discussion in the form of emotional intelligence. This research uses a quantitative experimental research method with data collection techniques in the form of questionnaires, interviews, observation and documentation.